Adhesively bonded connections in the context of timber engineering – A Review. Issue 4 (21st March 2017) - Vallée, Till; Tannert, Thomas; Fecht, Simon
ABSTRACT: If there is one domain of civil engineering in which adhesives are currently booming, then it is timber engineering. Natural adhesives have been used for centuries to structurally connect timber elements, a trend that culminated in the beginning of the 20th century with the introduction of glue-laminated beams. With the introduction of synthetic adhesives, and their increasing economic success after World War II, a wide range of products is now available that have the potential to free timber engineering from most of its structural and size limitations. This review article is intended to shed some light on the current state-of-the-art regarding adhesively bonded connections in the context of timber engineering. First, the relevant properties of timber as an adherend are discussed, then different – including several hybrid – approaches for structurally jointing timber are illustrated and finally, different design approaches are presented.